Prehospital trauma management: a national study of paramedic activities. Issue 1 (20th December 2004) - Sukumaran, S; Henry, J M; Beard, D; Lawrenson, R; Gordon, M W G; O'Donnell, J J; Gray, A J
Abstract : Objectives: The benefits of prehospital trauma management remain controversial. This study aimed to compare the processes of care and outcomes of trauma patients treated by paramedics, who are trained in advanced prehospital trauma care, with those treated by ambulance technicians. Methods: A six year prospective study was conducted of adult trauma patients attended to by the Scottish Ambulance Service and subsequently admitted to hospital. Prehospital times, interventions, triage, and outcomes were compared between patients treated by paramedics and those treated by technicians. Results: Paramedics attended more severely injured patients (16.5% versus 13.9%, p<0.001); they attended a higher proportion of patients with penetrating trauma (6.6% versus 5.7%, p = 0.014) and had longer prehospital times. Patients managed by paramedics were more likely to be taken to the intensive care unit, operating theatre or mortuary, (11.2% versus 7.8%, p<0.001) and had higher crude mortality rates (5.3% versus 4.5%, p = 0.07). However, no difference in mortality between the two groups was noted when corrected for age, Glasgow coma score and injury severity score. Conclusions: This large scale national study shows that paramedics show good triage skills and clinical judgement when managing trauma patients. However, the value of the individual interventions they perform could not be ascertained. Further controlled trials are necessary to determine the true benefits of advanced prehospital trauma life support.